Adhesion Reinforcement of Electrode–Electrolyte Interface in Flexible Electrochemical Energy Storage Devices - Xie, Xian; Wang, Qiuhong; Mushtaq, Faheem; Ao, Kelong; Zhao, Hong; Daoud, Walid A. (Nano-Micro Letters, 2026)
Wearable and deformable electronics are becoming increasingly essential components of modern healthcare and daily life. To power such devices, flexible electrochemical energy storage (FEES) plays a critical role. The practical performance of FEES is dominated by charge and mass transfer at the electrode-electrolyte interface, similar to many rigid battery technologies. However, a unique challenge for FEES is the durability of this interface under deformation. Herein, we present the first comprehensive review of the interface physics, unveiling the crucial role of interface adhesion in the mechanical endurance of FEES. By bridging adhesion physics, material chemistry, and device mechanics, adhesion reinforcement strategies are comprehensively discussed and quantitatively compared, providing multi-scale mechanisms for optimizing FFES interface - from nanoscale bond engineering to microscale surface topology, mechanical interlocking, and macroscale device design. Further, inspired by the synergetic effect of adhesion mechanisms, we propose potential research directions for durable electrode-electrolyte interfaces under dynamic deformation. We also revisit the evaluation of flexibility and electrochemical performance, proposing an application-driven bending index for device assessment. These insights on electrode-electrolyte interface physics of FEES will facilitate the flourishing future of flexible devices. Highlights: 1 This article is the first to systematically bridge adhesion physics, materials science, and device mechanics in flexible electrochemical energy storage, offering a multi-scale perspective from nanoscale bonds to macroscale design. 2 Comprehensive adhesion reinforcement strategies are classified and compared, with explicit emphasis on interfacial durability under dynamic deformation. 3 A novel application-driven bending index is introduced for standardizing the evaluation of flexible electrochemical energy storage flexibility, providing a practical framework for device assessment and comparison.